Difficulties in Academic Writing: Perspective of Graduate Students of UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan - Royani, Ida (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The purpose of this study was to determine what difficulties students come upon when learning to write English academically. The participants consisted of 54 graduate students entering in Academic Writing class during the academic year 2022- 2023. By using descriptive qualitative method, analysis of the data presented that English students encounter many difficulties and challenges in their academic writing activity, for instance establishment of process of writing stages, paragraph structure, presenting extended examples by statistics, and plagiarism. In brief, students’ difficulties in academic writing are in the writing process and discursive and non-discursive difficulties.